Foreign direct investment and industrial agglomeration: Evidence from China - HSU, Wen-Tai (Institutional Knowledge at Singapore Management University, 2020)
This paper studies the effect of foreign direct investment (FDI) on industrial ag-glomeration. Using the differential effects of FDI deregulation in 2002 in China on different industries, we find that FDI actually affects industrial agglomeration neg-atively. As FDI brings technological spillovers and various agglomeration benefits, other forces must be at work to drive our empirical finding. We propose a simple theory that FDI may discourage industrial agglomeration due to fiercer competition pressure. We find various evidence on this competition mechanism. We also examine an alternative theory based on spatial political competition, but find no evidence sup-porting it. On industrial growth, we find that FDI deregulation is conducive, but the dispersion induced by FDI deregulation reduces the positive effect of FDI on growth rate by 16 to 19%.